G77(P) Paediatric registrar review clinic: improving efficiency and attendance. (May 2019) - Chesover, A; Lim, C; Ingram, A
Abstract : A quality improvement project was undertaken within a district general hospital's paediatric department focussing on improving the efficiency and attendance rate of the Paediatric Registrar Review Clinic (RRC). Identified issues were high 'did not attend' (DNA) rate, inadequate referral information and inappropriate utilisation of the clinic. This resulted in either patients missing their review or attending when a more appropriate follow-up method was preferable, registrars challenged to efficiently run clinics without pertinent clinical information and ineffective utilisation of the department's clinic time. Data were collected through retrospective audit by registrars of nine consecutive RRC (November 2016 to January 2017) and included: number of patients booked, DNA, presence of referral information and feasibility for alternative follow-up. The results highlight high DNA, poor documentation of clinical problem and reason for review, and scope for alternative follow up suggesting inefficient use of clinic time. In response, four interventions were implemented: RRC guide listing best practices for referring. RRC appointment letter: reformatted explanation to families of clinic details, location and how to change appointments. RRC booking form: reformatted with adequate space for required referral information. Administrative changes: a. enable ward clerks to rearrange clinic appointments b. automated text message reminder one week prior to clinic. A repeat RRC audit of clinics (October 2017 to March 2018) was performed to measure the intervention's impact. Data collection methods were identical. Microsoft Excel was used for analysis by descriptive statistics for comparison between audits. See table 1 . The significant improvement in referral clinical details, decreased DNA rates and overall suitability of follow up method allowed more effective clinic preparation and clinical review by registrars and improved resource utilisation. This resulted from simple interventions without significant reorganisation of a clinical system. Successful development of a clinical system change requires involvement from the whole department to best understand challenges from different perspectives.